Validation of dynamic multi-criteria decision making design model for youth personal decision aid: expert reviews - Sarif, Siti Mahfuzah; Ibrahim, Norfiza; Shiratuddin, Norshuhada (Faculty of Computing, Universiti Teknologi Malaysia, 2016)
Developing computerized aids for youth decision making is much needed since this group are in the stage of facing various important decisions in life such as study and career, yet with lack of decision confidence at the same.For that reason, this study focuses on developing conceptual design model for the computerized personal decision aid for youth, known as YouthPDA.The proposed design model was reviewed by seven selected experts, in related areas, to ensure the appropriateness of its components and elements, the relevancy of the terminologies used, the logic of the flow, as well as its usability and practicality towards development of YouthPDA application.Discussions on the findings obtained from the expert review are included in this paper.Finally, a revised design model of YouthPDA is proposed as main guidance to develop YouthPDA application.